ANALISIS PENGARUH BEBERAPA VARIABEL FUNDAMENTAL KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM PERUSAHAAN TELEKOMUNIKASI YANG TERCATAT DI BURSA EFEK JAKARTA - Rajio Suwahyono; Hening Widi Oetomo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
The users of financial information need financial statements of company to analyze their financial conditions and performances. Financial ratios are useful measure for predicting the stock price. The study focused on the usefull of financial ratios in predicting stock price. The aim of the study is to examine whether  financial statements of company that are price earning ratio, price to book value, current ratio, debt to equity ratio, debt ratio, operating profit margin, net profit margin, total assets turnover, and return on asset simultaneously can influence the stock price and which ratios, partially can influence the stock price. The sample of this study is the telecommunication companies that listed in Jakarta Stock Exchange. Using purposive sampling, there are two companies that become sample that are PT Telekomunikasi Indonesia Tbk and PT Indosat Tbk. The study period is 10 years (1994 up to 2004). The data were analysed by multiple linier regression.The study show that financial statements of company that are price earning ratio, price on book value, current ratio, debt ratio, operating profit margin, net profit margin, and total assets turnover  simultaneously can influence the stock price. Partially price on book value, current ratio dan total asset turnover influence the stock price.